Rapid and scalable detection of synthetic mRNA byproducts using polynucleotide phosphorylase and polythymidine oligonucleotides - Francis Combes; Thanh-Huong Bui; Frida J. Pettersson; Sjoerd Hak (RNA Biology)
Production and storage of synthetic mRNA can introduce a variety of byproducts which reduce the overall integrity and functionality of mRNA vaccines and therapeutics. mRNA integrity is therefore designated as a critical quality attribute which must be evaluated with state-of-the-art analytical methods before clinical use. The current study first demonstrates the effect of heat degradation on transcript translatability and then describes a novel enzymatic approach to assess the integrity of conventional mRNA and long self-amplifying mRNA. By first hybridizing oligo-T to the poly(A) tail of intact mRNA and subsequently digesting the unhybridized RNA fragments with a 3’-5’ exoribonuclease, individual nucleotides can be selectively released from RNA fragments. The adenosine-based fraction of these nucleotides can then be converted into ATP and detected by luminescence as a sensitive indicator of mRNA byproducts. We developed a polynucleotide phosphorylase (PNPase)-based assay that offers fast and sensitive evaluation of mRNA integrity, regardless of its length, thus presenting a novel and fully scalable alternative to chromatographic-, electrophoresis-, or sequencing-based techniques.